Analysis of Ostwald-de Waele Power-Law Nanofluid Flow in a Non-Darcy Porous Medium with an Efficient Spectral Algorithm - Ramreddy, Ch.; Abhinava, Srivastav (Discontinuity, Nonlinearity, and Complexity, 2026)
An Ostwald-de Waele power-law nanofluid flow over a truncated cone in a non-Darcy porous medium is analysed numerically. Different volume fractions of Ti-alloy and MWCNTs nanoparticles are considered to obtain their complete influence on physical profiles. Error analysis is conducted and the results in special cases are also compared with previously published papers. Higher velocity is noticed for dilatant nanofluid when compared to pseudo-plastic nanofluid and it is decreased with nanoparticle volume fractions increment. This problem is very helpful in aerospace and medical sectors due to involvement of Ti-alloys in making aircraft turbines, orthopaedical instruments etc.